2020
DOI: 10.21203/rs.3.rs-28049/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased MLKL mRNA level in the PBMCs is correlated with autoantibody production, renal involvement and SLE disease activity

Abstract: Background: Necroptosis is a form of regulated necrosis that is involved in various autoimmune diseases. Mixed lineage kinase domain-like pseudokinase (MLKL) has been identified as a key executor of necroptosis, however, the significance of MLKL in peripheral blood mononuclear cells (PBMCs) of systemic lupus erythematosus (SLE) has not been investigated. In this study, we aimed to determine the mRNA level of MLKL in PBMCs and examine its relationship with clinical features and serological parameters in SLE. Me… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Overactivated necroptosis has been reported in many types of diseases affecting the tissue, including ischemia-reperfusion injury, neurodegenerative diseases, and inflammation (8). Intriguingly, necroptosis has also recently been found to be dysregulated in autoimmune diseases (23)(24)(25)(26), suggesting that necroptosis plays a vital role in autoimmune diseases by controlling the fate of a variety of cells.…”
Section: Discussionmentioning
confidence: 99%
“…Overactivated necroptosis has been reported in many types of diseases affecting the tissue, including ischemia-reperfusion injury, neurodegenerative diseases, and inflammation (8). Intriguingly, necroptosis has also recently been found to be dysregulated in autoimmune diseases (23)(24)(25)(26), suggesting that necroptosis plays a vital role in autoimmune diseases by controlling the fate of a variety of cells.…”
Section: Discussionmentioning
confidence: 99%
“…BAFF is a type II transmembrane protein encoded by human chromosome 13q34, which is mainly expressed in peripheral blood mononuclear cells, lymph nodes, spleen, and thymus, but lowly expressed in the small intestine, pancreas, placenta, and lung [10,11]. Abundant evidence demonstrated that BAFF is involved in pathogenesis of systemic lupus erythematosus (SLE), which is a prototype autoimmune disease affecting multiple organ systems [12][13][14][15][16][17][18]. In these patients, a large number of autoantibodies are produced and the deposition of immune complexes occurs in multiple organs, especially in kidneys [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…BAFF is a type II transmembrane protein encoded by human chromosome 13q34, which is mainly expressed in peripheral blood mononuclear cells, lymph nodes, spleen, and thymus, but lowly expressed in the small intestine, pancreas, placenta, and lung [10,11]. Abundant evidence demonstrated that BAFF is involved in pathogenesis of systemic lupus erythematosus (SLE), which is a prototype autoimmune disease affecting multiple organ systems [12][13][14][15][16][17][18]. In these patients, a large number of autoantibodies are produced and the deposition of immune complexes occurs in multiple organs, especially in kidneys [19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%